Strategi Pengelolaan Siswa ABK Jenis Tunagrahita di Kelas Inklusi - Rahmah Nurfitriani; Muhammad Almi Hidayat (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The application of inclusive education in Indonesia is a way for the government to continue to provide educational services to the community openly and non-discriminatively, both for typical children and children with special needs, one of which is mentally disabled children. This study aims to understand about 1) Characteristics of Tunagrahita Students in the Junrejo 01 SDN inclusion class and 2) Tunagrahita Student Management Strategies in the Junrejo 01 SDN inclusion class in Batu. This research method is a qualitative approach, the type of case study located at SDN Junrejo 01 Kota Batu for ABK students with mental disabilities class II inclusion in the 2019 school year. This study indicates that the mentally disabled students have IQ characteristics below between 70 -80, have the same physical condition as an average child, have high imagination despite weak language skills, and have low self-confidence. From the motor aspect, the mentally retired student can perform psychomotor activities like other students. The mental retardation student management strategies are 1) Applying cooperative learning models, 2) Learning with the Peer Teaching method, 3) Giving the same task in study groups, 4) Assigning homework specifically for mentally disabled people, 5) Using educational games in learning, 6) Giving Rewards for Group and Personal Achievement 7) Environmental Therapy to Train the Solidarity of Retarded Students, 8) Teachers Establish Cooperative Relations with Parents of Tunagrahita students.